Electrochemical and Electronic Devices
By applying a functional layer with organic polymers and inorganic particles to the current collector region of secondary battery electrodes, the issues of liquid retention, safety, and energy density loss are addressed, resulting in improved performance and cycle life.
Patent Information
- Application Number
- JP2024556739
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-04-15
AI Technical Summary
Secondary batteries face challenges with liquid retention, safety characteristics, and energy density loss due to high compression densities of electrode materials and excessive electrolyte release, leading to swelling and reduced cycle life.
The application of a functional layer containing organic polymers and inorganic particles to the current collector region of the electrode assembly, which absorbs free electrolyte, improves liquid retention, prevents swelling, and enhances safety by avoiding internal short circuits.
This solution achieves high liquid retention, improved safety characteristics, and reduced energy density loss, while maintaining good cycling characteristics by controlling the thickness and particle size distribution of the functional layer.
Smart Images

Figure 2025510848000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the storage field, and in particular to electrochemical and electronic devices. [Background technology]
[0002] Secondary batteries (electrochemical devices) have advantages such as high energy density, good cycle characteristics, environmental friendliness, safety, and no memory effect, and are therefore applied in fields such as portable electronic products, electric vehicles, and energy storage. First, electrolyte plays an important role in the cycle life of secondary batteries, and in order to ensure a long cycle life of the battery, it is necessary to inject excess electrolyte into the battery to compensate for the consumption of electrolyte during the cycle. Second, in order to improve the energy density of the battery, the compression density of the positive and negative electrode pieces continues to increase, and due to the high compression density, the amount of electrolyte absorbed by the positive and negative electrode active materials becomes less and less, and the unabsorbed electrolyte is liberated inside the packaging bag (e.g., aluminum plastic film), which makes the appearance of the battery easily bulge. In addition, in order to improve the safety characteristics of the secondary battery, the energy density of the secondary battery is often lost. Therefore, there is an urgent need to provide a technical means that can significantly improve the electrolyte retention and safety characteristics of the secondary battery. Summary of the Invention
[0003] In view of the shortcomings of the prior art, the present invention provides an electrochemical device and an electronic device including the electrochemical device, which can simultaneously have high liquid retention capacity, high safety characteristics and good cycle characteristics.
[0004] In a first aspect, the present invention provides an electrochemical device comprising an electrode assembly, the electrode assembly comprising an electrode piece, the electrode piece comprising a current collector, the current collector comprising a first region and a second region, an active material layer being provided in the first region, and a functional layer being provided in the second region, the functional layer comprising an organic polymer and inorganic particles, wherein when a thickness of the functional layer is H1, H1 satisfies 1 μm≦H1≦15 μm, and Dv90 of the inorganic particles satisfies 1 μm≦Dv90≦4.5 μm. According to the research of the inventors of the present invention, by applying a functional layer containing an organic polymer and inorganic particles to the current collector region of the pole piece where the active material is not applied, the organic polymer in the functional layer can absorb the liberated electrolyte, thereby improving the liquid retention capacity of the electrochemical device, and preventing the surface irregularities of the electrochemical device caused by the excess electrolyte being liberated unevenly inside the packaging bag (e.g., aluminum plastic film), and further improving the appearance flatness of the electrochemical device, reducing its energy density loss, and improving its later cycle characteristics. Meanwhile, the inorganic particles in the functional layer can avoid defects caused by internal short circuits that occur when the electrochemical device is penetrated by an external force, and further effectively improve the safety characteristics of the electrochemical device in a penetration test. The Dv90 of the inorganic particles affects the thickness of the functional layer. If the Dv90 of the inorganic particles is too large, the thickness of the functional layer will be too large. And if the thickness of the functional layer is too large, the energy density of the electrochemical device will be reduced. By controlling the thickness of the functional layer and the Dv90 of the inorganic particles within the above ranges, the present invention enables the electrochemical device to have low energy density loss and good cycle characteristics while satisfying high liquid retention capacity and safety characteristics.
[0005] In some embodiments, the functional layer can absorb the electrolyte. According to some embodiments of the present invention, H1 satisfies 5 μm≦H1≦15 μm. The functional layer is mainly used to absorb the electrolyte. If the thickness of the functional layer is too low, the electrolyte retention rate of the functional layer will be low, which is disadvantageous to improving the appearance of the electrochemical device and improving the characteristics at the later stage of cycles.
[0006] According to some embodiments of the present invention, the Dv10 of the inorganic particles satisfies 0.1 μm≦Dv10≦0.8 μm. In some embodiments, the Dv50 of the inorganic particles satisfies 0.5 μm≦Dv50≦2.0 μm. In some embodiments, the Dv90 of the inorganic particles satisfies 1 μm≦Dv90≦2.5Dv50.
[0007] According to some embodiments of the present invention, the coverage of the functional layer in the second region is 80% to 100%. When the coverage is in the above range, the safety characteristics of the electrochemical device can be improved and the liquid retention capacity of the electrochemical device can be further improved.
[0008] According to some embodiments of the present invention, the inorganic particles include at least one of boehmite, diaspore, alumina, barium sulfate, calcium sulfate, and calcium silicate.
[0009] According to some embodiments of the present invention, the organic polymer comprises a polymer of at least one of an acrylic monomer, an acrylate monomer, and a styrenic monomer.
[0010] According to some embodiments of the present invention, the swelling degree of the functional layer is 200% to 800%. If the swelling degree of the functional layer is less than 200%, the electrolyte retention rate of the functional layer is low, which is disadvantageous in improving the appearance of the electrochemical device. If the swelling degree of the functional layer is more than 800%, the stability of the functional layer itself is poor, and it is easy to be released during cycles, which further affects the effect of improving the appearance and the electrical properties of the subsequent cycles. In some embodiments, the swelling degree of the functional layer is 300% to 600%.
[0011] According to some embodiments of the present invention, the functional layer comprises a substance having an exothermic peak in the range of 280°C to 460°C according to thermogravimetry, and this substance can be a polymer consisting of at least one of styrene-acrylate copolymer, acrylic acid, methacrylic acid, methyl methacrylate, etc.
[0012] According to some embodiments of the present invention, based on the weight of the functional layer, the weight percentage of the organic polymer is 20% to 90%.
[0013] According to some embodiments of the present invention, the adhesive strength between the functional layer and the current collector is 100 N / m to 600 N / m.
[0014] According to some embodiments of the present invention, a non-destructive ultrasonic intelligent diagnostic system is used to measure, and ultrasonic waves are transmitted to the electrochemical device along the thickness direction of the electrochemical device to obtain a signal feedback distribution map of the ultrasonic waves of the electrochemical device, and the area ratio of the area of the region where the ultrasonic signal intensity is 1333 mV or more is 30% to 95% based on the area of the electrochemical device in the signal feedback distribution map. Ultrasonic waves are mechanical waves and require a medium to propagate. If there is no electrolyte infiltration between the electrode materials, the ultrasonic waves can only propagate through direct contact between the electrode material particles, and the presence of irregular particles causes a large amount of reflection and refraction of the ultrasonic waves, and the signal intensity is significantly attenuated. On the other hand, when the electrolyte completely infiltrates the electrode material, the liquid environment provides a good propagation path for the ultrasonic waves, and most of the ultrasonic waves are not interfered with by particles, thereby ensuring the strength of the signal. Therefore, in the measurement by the non-destructive ultrasonic intelligent diagnostic system, the signal feedback intensity of the ultrasonic waves at each point of the electrochemical device can well characterize the electrolyte distribution and infiltration situation inside the electrochemical device. The higher the percentage of areas with high signal intensity, the more uniform the distribution of the electrolyte within the electrochemical device.
[0015] According to some embodiments of the present invention, the electrochemical device has a flatness of 0-0.5 mm.
[0016] According to some embodiments of the present invention, the electrode assembly is a wound electrode assembly, in which a second region is provided at the winding start end and the winding end of the current collector, and a functional layer is provided in the second region at the winding end.
[0017] In a second aspect, the present invention provides an electronic device comprising an electrochemical device of the first aspect.
[0018] The present invention improves the liquid retention capacity of an electrochemical device by applying a functional layer containing an organic polymer and inorganic particles to the current collector area of a pole piece on which no active material is applied, prevents the surface of the electrochemical device from becoming uneven due to excess electrolyte being unevenly released inside a packaging bag (e.g., aluminum plastic film), improves the external flatness of the electrochemical device, reduces its energy density loss, and improves its later cycle characteristics. On the other hand, it can avoid defects caused by internal short circuits that occur when the electrochemical device is pierced by an external force, and effectively improves the safety characteristics of the electrochemical device in a piercing test. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram of an electrode strip in an electrochemical device according to some embodiments of the present invention, where: 1 - current collector, 2 - active material layer, 3 - functional layer. [Diagram 2] FIG. 2 is a schematic diagram of a wound electrode assembly in an electrochemical device according to some embodiments of the present invention, where: 1 - current collector, 2 - active material layer, 3 - functional layer, 4 - end of winding, 5 - beginning of winding, and the functional layer is provided at the end of winding of the current collector. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are used to illustrate the present invention and do not limit the scope of the present invention.
[0021] 1. Electrochemical equipment The present invention provides an electrochemical device, the electrochemical device comprising an electrode assembly, the electrode assembly comprising an electrode piece, the electrode piece comprising a current collector, the current collector comprising a first region and a second region, an active material layer being provided in the first region, a functional layer being provided in the second region, the functional layer comprising an organic polymer and inorganic particles, the thickness of the functional layer being H1, H1 being 1 μm≦H1≦15 μm, and the Dv90 of the inorganic particles being 1 μm≦Dv90≦4.5 μm. According to the research of the inventors of the present invention, by applying a functional layer comprising an organic polymer and inorganic particles to the current collector region of the electrode piece where the active material is not applied, the organic polymer in the functional layer can absorb the liberated electrolyte, thereby improving the liquid retention capacity of the electrochemical device, and preventing the surface unevenness of the electrochemical device caused by the excess electrolyte being liberated unevenly inside the packaging bag (e.g., aluminum plastic film), and further improving the appearance flatness of the electrochemical device, reducing its energy density loss, and improving its late cycle characteristics. On the other hand, the inorganic particles in the functional layer can prevent defects caused by internal short circuits that occur when the electrochemical device is penetrated by an external force, and can effectively improve the safety characteristics of the electrochemical device in a penetration test. By controlling the thickness of the functional layer and the Dv90 of the inorganic particles within the above ranges, the present invention can provide an electrochemical device with low energy density loss and good cycle characteristics while satisfying high liquid retention capacity and safety characteristics.
[0022] In the present invention, the "second region" refers to a blank region on the current collector where no active material layer is provided.
[0023] According to some embodiments of the present invention, the Dv90 of the inorganic particles is 1.0 μm, 1.2 μm, 1.5 μm, 1.7 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3.0 μm, 3.1 μm, 3.3 μm, 3.5 μm, 3.7 μm, 3.9 μm, 4.0 μm, 4.2 μm, 4.4 μm, or a range consisting of any two of these values. The Dv90 of the inorganic particles affects the thickness of the functional layer. If the Dv90 of the inorganic particles is too large, the thickness of the functional layer will be too large. And if the thickness of the functional layer is too large, the energy density of the electrochemical device will be reduced.
[0024] According to some embodiments of the present invention, the Dv10 of the inorganic particles satisfies 0.1 μm≦Dv10≦0.8 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or a range consisting of any two of these values. In some embodiments, the Dv50 of the inorganic particles satisfies 0.5 μm≦Dv50≦2.0 μm, for example, 0.5 μm, 0.7 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.9 μm, or a range consisting of any two of these values. In some embodiments, the Dv90 of the inorganic particles satisfies 1 μm≦Dv90≦2.5Dv50.
[0025] In the present invention, Dv90 indicates that 90% of the particles in the volumetric particle size distribution of the inorganic particles are smaller than this value. Dv50 indicates that 50% of the particles in the volumetric particle size distribution of the inorganic particles are smaller than this value. Dv10 indicates that 10% of the particles in the volumetric particle size distribution of the inorganic particles are smaller than this value.
[0026] According to some embodiments of the present invention, the thickness H1 of the functional layer is 1.5 μm, 2.0 μm, 3.0 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, or a range consisting of any two of these values. In some embodiments, the functional layer can absorb the electrolyte. The functional layer is mainly used to absorb the electrolyte. If the thickness of the functional layer is too low, the electrolyte retention rate of the functional layer will be low, which is disadvantageous to improving the appearance of the electrochemical device and improving the characteristics at the later stage of the cycle. If the thickness of the functional layer is too large, it reduces the energy density of the electrochemical device. In some embodiments, H1 satisfies 5 μm≦H1≦15 μm.
[0027] According to some embodiments of the present invention, the coverage of the functional layer in the second region is 80% to 100%. When the coverage is in the above range, the safety characteristics of the electrochemical device can be improved and the liquid retention capacity of the electrochemical device can be further improved.
[0028] In the present invention, the coverage of the functional layer in the second region indicates the degree of coverage of the functional layer on the surface of the second region. The coverage of the functional layer in the second region can be determined as follows: At (25±3)°C, the pole piece coated with the functional layer is removed from the electrochemical device and placed in an oven at 85°C to dry, and the area W3 of the functional layer and the total area W2 of all blank current collectors in the pole piece are measured, respectively, and the coverage of the functional layer in the second region is W3 / W2×100%.
[0029] According to some embodiments of the present invention, the inorganic particles include at least one of boehmite, diaspore, alumina, barium sulfate, calcium sulfate, and calcium silicate.
[0030] According to some embodiments of the present invention, the organic polymer comprises a polymer of at least one of an acrylic monomer, an acrylate monomer, and a styrenic monomer.
[0031] In some embodiments, the acrylic monomer comprises at least one compound represented by Formula I.
[0032] [ka]
[0033] where R1 is hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 According to some embodiments of the present invention, R1 is selected from C1-C6 alkyl groups, and halogen-substituted C1-C6 alkyl groups. In some embodiments of the present invention, R1 is selected from methyl, ethyl, fluorine-containing ethyl, propyl, fluorine-containing propyl, butyl, fluorine-containing butyl, pentyl, and fluorine-containing pentyl.
[0034] In some embodiments, the acrylic monomer comprises at least one of acrylic acid, methacrylic acid, and ethylacrylic acid.
[0035] In some embodiments, the acrylate monomer comprises at least one compound represented by formula II.
[0036] [ka]
[0037] R2 is hydrogen, C1-C 10 Alkyl groups and halogen-substituted C1-C 10 alkyl group, R3 is selected from C1 to C 10 Alkyl groups, halogen-substituted C1-C 10According to some embodiments of the present invention, R2 is selected from hydrogen, C1-C6 alkyl groups, and halogen-substituted C1-C6 alkyl groups, and R3 is selected from C1-C6 alkyl groups and halogen-substituted C1-C6 alkyl groups. In some embodiments of the present invention, R2 is selected from hydrogen, methyl, ethyl, and propyl, and R3 is selected from methyl, ethyl, fluorine-containing ethyl, propyl, fluorine-containing propyl, butyl, fluorine-containing butyl, pentyl, and fluorine-containing pentyl.
[0038] In some embodiments, the acrylate monomers include at least one of methyl acrylate, methyl methacrylate, ethyl methyl acrylate, ethyl acrylate, ethyl methacrylate, ethyl ethyl acrylate, propyl acrylate, propyl methacrylate, ethyl propyl acrylate, butyl acrylate, butyl methacrylate, ethyl butyl acrylate, pentyl methacrylate, and pentyl acrylate.
[0039] According to some embodiments of the present invention, the styrenic monomer comprises at least one compound represented by formula III:
[0040] [ka]
[0041] Here, n is an integer of 1 to 5, for example, 2, 3, or 4; each R4 is the same or different and independently represents hydrogen, C1 to C 10 Alkyl groups and halogen-substituted C1-C 10 alkyl group, R5 and R6 are the same or different and each independently represent hydrogen, C1 to C 10 Alkyl groups and halogen-substituted C1-C 10 According to some embodiments of the present invention, R4 is selected from hydrogen, a C1-C6 alkyl group, and a halogen-substituted C1-C6 alkyl group; R5 and R6 are the same or different and each independently are selected from a C1-C6 alkyl group.16 In some embodiments of the present invention, R4, R5, and R6 are each independently selected from hydrogen, methyl, ethyl, and propyl.
[0042] In some embodiments, the styrenic monomer comprises at least one of styrene, methylstyrene, 2-methylstyrene, and 2,4-dimethylstyrene.
[0043] According to some embodiments of the present invention, the raw materials forming the organic polymer include at least one of an acrylic latex, a styrene acrylic latex, and an acrylate latex. In some embodiments, the organic polymer includes at least one of an acrylic latex, a styrene acrylic latex, and an acrylate latex.
[0044] According to some embodiments of the present invention, the raw materials forming the organic polymer include acrylic latex and styrene acrylic latex. In some embodiments, based on the total weight of the acrylic latex and the styrene acrylic latex, the weight percentage of the acrylic latex is 50% to 90%, and the weight percentage of the styrene acrylic latex is 10% to 50%.
[0045] According to some embodiments of the present invention, the swelling degree of the functional layer is 200% to 800%. In some embodiments, the swelling degree of the functional layer is 220%, 250%, 270%, 320%, 350%, 370%, 390%, 400%, 420%, 450%, 470%, 500%, 520%, 540%, 570%, 600%, 620%, 650%, 670%, 700%, 720%, 750%, 770%, or a range consisting of any two of these values. If the swelling degree of the functional layer is less than 200%, the electrolyte retention rate of the functional layer is low, which is disadvantageous in improving the appearance of the electrochemical device. If the swelling degree of the functional layer is more than 800%, the stability of the functional layer itself is poor, and it is easy to be released during cycles, which further affects the effect of improving the appearance and the electrical properties of the subsequent cycles. In some embodiments, the swelling degree of the functional layer is between 300% and 600%.
[0046] According to some embodiments of the present invention, the functional layer includes a substance having an exothermic peak in the range of 280°C to 460°C according to thermogravimetry.
[0047] According to some embodiments of the present invention, the weight percentage of the organic polymer is 20% to 90% based on the weight of the functional layer, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or a range consisting of any two of these values. In some embodiments, the weight percentage of the organic polymer is 40% to 70% based on the weight of the functional layer.
[0048] According to some embodiments of the present invention, the adhesive strength between the functional layer and the current collector is 100 N / m to 600 N / m.
[0049] According to some embodiments of the present invention, a non-destructive ultrasonic intelligent diagnostic system is used to measure, and ultrasonic waves are transmitted to the electrochemical device along the thickness direction of the electrochemical device to obtain a signal feedback distribution map of the ultrasonic waves of the electrochemical device, and the area ratio of the area of the region where the ultrasonic signal intensity is 1333 mV or more is 30% to 95% based on the area of the electrochemical device in the signal feedback distribution map. Ultrasonic waves are mechanical waves and require a medium to propagate. If there is no electrolyte infiltration between the electrode materials, the ultrasonic waves can only propagate through direct contact between the electrode material particles, and the presence of irregular particles causes a large amount of reflection and refraction of the ultrasonic waves, and the signal intensity is significantly attenuated. On the other hand, when the electrolyte completely infiltrates the electrode material, the liquid environment provides a good propagation path for the ultrasonic waves, and most of the ultrasonic waves are not interfered with by particles, thereby ensuring the strength of the signal. Therefore, in the measurement by the non-destructive ultrasonic intelligent diagnostic system, the signal feedback intensity of the ultrasonic waves at each point of the electrochemical device can well characterize the electrolyte distribution and infiltration situation inside the electrochemical device. The higher the percentage of areas with high signal intensity, the more uniform the distribution of the electrolyte within the electrochemical device.
[0050] According to some embodiments of the present invention, the percentage of the area of the region where the signal intensity is 1333 mV or more is 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 57%, 60%, 63%, 65%, 67%, 70%, 73%, 75%, 77%, 80%, 83%, 85%, 87%, 90%, 92%, 94%, or a range consisting of any two of these values. In some embodiments, the percentage of the area of the region where the signal intensity is 1333 mV or more is 50% to 95%.
[0051] According to some embodiments of the present invention, the electrolyte retention rate of the functional layer is 40% to 120%. In some embodiments, the electrolyte retention rate of the functional layer is 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 105%, 110%, 115%, or a range consisting of any two of these values. If the shipping appearance of the electrochemical device meets the requirements, increasing the electrolyte retention rate is advantageous in improving the cycle stability of the electrochemical device in the later stages.
[0052] According to some embodiments of the present invention, the electrochemical device has a flatness of 0-0.5 mm.
[0053] According to some embodiments of the present invention, the electrode assembly is a wound electrode assembly, in which a second region is provided at the winding start end and the winding end of the current collector, and a functional layer is provided in the second region at the winding end.
[0054] According to some embodiments of the present invention, the active material layer is a positive electrode active material layer and / or a negative electrode active material layer.
[0055] According to some embodiments of the present invention, the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive agent. In some embodiments, the positive electrode active material can include at least one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, lithium manganese spinel type manganate, lithium nickel manganate spinel type, and lithium titanate. In some embodiments, the binder can include at least one of various polymers as adhesives, such as polyvinylidene fluoride, polytetrafluoroethylene, polyolefin, sodium carboxymethylcellulose, lithium carboxymethylcellulose, modified polyvinylidene fluoride, modified SBR rubber, and polyurethane. In some embodiments, any conductive material can be used as the conductive agent as long as it does not undergo chemical changes. Examples of the conductive agent include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers containing copper, nickel, aluminum, silver, and the like; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0056] According to some embodiments of the present invention, the negative electrode active material layer includes a negative electrode active material, a binder, and a conductive agent. In some embodiments, the negative electrode active material can include a material that reversibly absorbs / desorbs lithium ions, lithium metal, a lithium metal alloy, or a transition metal oxide. In some embodiments, the negative electrode active material includes at least one of a carbon material and a silicon-based material, the carbon material includes at least one of graphite and hard carbon, and the silicon-based material includes at least one of silicon, silicon oxide, silicon carbon compound, and silicon alloy. In some embodiments, the binder includes at least one of styrene butadiene rubber, polyacrylic acid, polyacrylate, polyimide, polyamide imide, polyvinylidene fluoride, polydifluoroethylene, polytetrafluoroethylene, water-based acrylic resin, polyvinyl formal, and styrene-acrylic acid copolymer resin. In some embodiments, any conductive material can be used as the conductive agent as long as it does not undergo a chemical change. In some embodiments, the conductive material comprises at least one of conductive carbon black, acetylene black, carbon nanotubes, ketjen black, conductive graphite, and graphene.
[0057] According to some embodiments of the present invention, the current collector is a positive electrode current collector and / or a negative electrode current collector. In some embodiments, the positive electrode current collector can be a metal foil or a composite current collector. For example, the positive electrode current collector can be an aluminum foil. The composite current collector is formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy) on a polymer substrate. In some embodiments, the negative electrode current collector can be a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a nickel foam, a copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0058] The electrode assembly of the present invention further includes a separator. The material and shape of the separator used in the electrode assembly of the present invention are not particularly limited and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic material formed of a material stable to the electrolyte of the present invention. For example, the separator can include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, film, or composite film having a porous structure. The material of the substrate layer is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, the material of the substrate layer can be selected from a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite film.
[0059] A surface treatment layer is provided on at least one surface of the base layer. The surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic layer.
[0060] The inorganic layer includes inorganic particles and a binder. The inorganic particles are at least one selected from alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is at least one selected from polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polymethylmethacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.
[0061] The polymer layer includes a polymer, and the polymer material is at least one selected from polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinylalkoxy, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0062] The electrochemical device of the present invention further comprises an electrolyte. The electrolyte used in the present invention can be any electrolyte known in the art.
[0063] In some embodiments, the electrolyte comprises an organic solvent, a lithium salt, and optional additives. The organic solvent used in the electrolyte of the present invention can be any organic solvent used as a solvent for electrolytes known in the art. The electrolyte used in the electrolyte of the present invention is not limited and can be any electrolyte known in the art. The additive used in the electrolyte of the present invention can be any additive used as an electrolyte additive known in the art. In some embodiments, the organic solvent includes, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, or ethyl propionate. In some embodiments, the organic solvent includes at least one of ether solvents, such as 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of organic lithium salts and inorganic lithium salts. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF), lithium tetrafluoroborate (LiBF), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonimide) LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalato)borate LiB(C2O4)2 (LiBOB), or lithium difluoro(oxalato)borate LiBF2(C2O4) (LiDFOB).
[0064] In some embodiments, the electrochemical device of the present invention includes, but is not limited to, any type of primary battery, secondary battery, or capacitor. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a sodium ion secondary battery, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery. 2.Electronic equipment
[0065] The present invention further provides an electronic device comprising an electrochemical device according to the first aspect of the present invention.
[0066] The electronic device or device of the present invention is not particularly limited. In some embodiments, the electronic device of the present invention includes, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a portable facsimile, a portable copy machine, a portable printer, a stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disk, a transceiver, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, an auxiliary bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a strobe, a camera, a large household storage battery, and a capacitor.
[0067] Reagents, materials and equipment used in the following examples and comparative examples are commercially available unless otherwise stated. Examples and Comparative Examples
[0068] Preparation of functional layer slurry The binder (specific composition is shown in the table below), inorganic particles (specific composition is shown in the table below), and solvent were mixed uniformly to prepare a slurry with a binder to inorganic particles mass ratio of 17:3. This slurry needs to be controlled so that the viscosity is 200-3000 mPa·S and the solid content is 35%-50%. The solvent is selected according to the type of binder. If the binder is aqueous, an aqueous solvent (e.g., deionized water, etc.) can be adopted, while if the binder is oil-based, an oil-based solvent (e.g., N-methylpyrrolidone, etc.) can be adopted.
[0069] Preparation of electrode strips The slurry prepared above was applied to the target area of the current collector (the winding end of the current collector as shown in Figure 2), the solvent was dried, and an electrode piece coated with a functional layer was obtained. A slurry containing an active material was applied to the area not coated with the functional layer, and the electrode piece was obtained through further drying and roll pressing.
[0070] The slurry containing the active material was a positive electrode active material slurry or a negative electrode active material slurry. Specifically, the positive electrode active material slurry was prepared as follows. Lithium cobalt oxide, conductive carbon, and polyvinylidene fluoride were mixed in a mass ratio of 96:2:2, and N-methyl-2-pyrrolidone (NMP) was added to prepare a slurry. The negative electrode active material slurry was prepared as follows. Graphite, styrene butadiene rubber, and sodium carboxymethylcellulose were mixed in a mass ratio of 98:1:1, and deionized water was added to prepare a slurry.
[0071] Preparation of secondary batteries The positive electrode, separator (PE porous polymer film), and negative electrode were stacked in this order, and the separator was placed between the positive and negative electrodes to provide a separating effect, and then wound to obtain an electrode assembly. The electrode assembly was placed in an exterior aluminum plastic film, and electrolyte (a solution in which the solvent is EC and DMC in a volume ratio of 1:1 and the concentration of LiPF6 by mass is 12.5% based on the mass of the electrolyte) was injected, and the secondary battery was prepared through processes such as vacuum packaging, standing, chemical formation, and shaping.
[0072] Measurement method 1. Thickness of functional layer a) The pole piece coated with the functional layer was removed from the secondary battery in an environment of (25±3)°C. If there was another coating layer on the opposite side of the current collector to which the functional layer was applied, it was necessary to remove that coating layer by a physical or chemical method so as not to damage the functional layer.
[0073] b) The pole piece (including the current collector) on which the functional layer was applied was placed in an oven at 85°C and dried for 30 to 60 minutes to ensure that all the electrolyte inside the functional layer was dried, and an ultra-high precision micrometer was used to measure the thickness of at least 10 points on the pole piece (including the current collector) on which the dried functional layer was applied, and the average thickness value of all measured points was taken as T1.
[0074] c) The functional layer was removed by a physical or chemical method without damaging the corresponding current collector, and the thickness of the current collector on which the functional layer was applied was measured at least in 10 places using an ultra-high precision micrometer, and the average thickness value of all measured places was taken as T0.
[0075] d) The thickness of the functional layer was (T1-T0).
[0076] 2. Measurement of inorganic particle size The particle size measurement method was based on GB / T 19077-2016. The measurement device used was a Malvern Mastersizer 3000. The refractive index of the particles used in the measurement was 1.8, and measurements were taken three times for each sample. The particle size was finally calculated by taking the average value of the three measurements, and was designated as Dv10, Dv50, and Dv90.
[0077] 3. Thermogravimetry of functional layer The pole piece coated with the functional layer was removed from the secondary battery in an environment of (25±3)° C. The powder was scraped off from the pole piece and placed in a thermogravimeter with a temperature range of 20° C. to 600° C., a heating rate of 5° C. / min, and a nitrogen gas atmosphere.
[0078] 4. Average coverage of the functional layer in the second region The pole piece coated with the functional layer was removed from the electrochemical device in an environment of (25±3)° C. It was then placed in an oven at 85° C. to dry, and the area W3 of the functional layer and the total area W2 of all blank current collectors in the pole piece were measured, and the average coverage of the functional layer in the second region was calculated as W3 / W2×100%.
[0079] 5. Ultrasonic detection Using a non-destructive ultrasonic intelligent diagnostic device (type: UBSC-LD), ultrasonic waves were transmitted to the secondary battery along the thickness direction of the secondary battery (50MHZ, 400mV), and a signal feedback distribution map for the ultrasonic waves at each point on the battery was obtained. Using integration software such as JMP software, the total area S of the battery in the signal feedback distribution map was calculated, the area where the signal strength was ≧1333mV was defined as S1, and the ratio of the area where the signal strength was ≧1333mV to the total area S of the battery was defined as S1 / S×100%.
[0080] 6, Adhesive strength The adhesion between the functional layer and the current collector was measured by the 90° peel method using a tensile tester manufactured by Gotech Testing Machines Inc. Specifically, The pole piece of the secondary battery where the functional layer was applied was cut into a strip, and a part of the pole piece was attached to a steel plate with double-sided tape from one end of the pole piece along the length direction. The steel plate was then fixed at the corresponding position in a tensile tester manufactured by Gotech Testing Machines Inc., and the pole piece that was not attached to the steel plate was pulled up and clamped in a chuck either via a connector or directly. When the chuck pulling force became greater than 0kgf and less than 0.02kgf, testing with the tensile tester manufactured by Gotech Testing Machines Inc. began, and the average pulling force in the stable region was finally measured as the adhesion strength between the functional layer and the current collector.
[0081] 7, Electrolyte retention rate a) In an environment of (25±3)℃, the pole piece coated with the functional layer was removed from the secondary battery. If there was another coating layer on the opposite side of the current collector coated with the functional layer, it was necessary to remove that coating layer by a physical or chemical method without damaging the functional layer. Then, the current collector coated with the functional layer was cut with a cutting machine.
[0082] b) Using an electronic balance, each of the current collectors (including the current collector) on which the functional layer was applied and cut as described above was weighed at least three times, and the weights were designated m1, m2, m3, etc., and the average value m was calculated.
[0083] c) The current collector (including the current collector) coated with the functional layer weighed above was placed in an oven at 85°C and dried for 30 to 60 minutes to ensure that all of the electrolyte inside the functional layer was dried. The weight of each dried current collector coated with the functional layer was then weighed at least three times and designated as M1, M2, M3..., and the average value M was calculated.
[0084] d) The functional layer was removed by a physical or chemical method so as not to damage the corresponding current collector, and the weight of the corresponding current collector was weighed at least three times, which were designated as G1, G2, G3, ..., and the average value G was calculated.
[0085] e) The electrolyte retention rate of the functional layer was determined as R = (mM) / (MG) x 100%.
[0086] 8. Swelling degree a) Preparation of adhesive film In an environment of (25±3)℃, the pole piece coated with the functional layer was removed from the secondary battery. If there was another coating layer on the opposite side of the current collector coated with the functional layer, it was necessary to remove the coating layer by a physical or chemical method so as not to damage the functional layer. Then, the current collector coated with the functional layer was cut with a cutting machine, immersed in dimethyl carbonate (DMC) to remove the electrolyte dissolved in the functional layer, taken out and dried, and further placed in water to dissolve the functional layer and become a solution. This solution was placed in a mold for preparing an adhesive film, and if there were any air bubbles, they were pulled out and removed. The mold was placed in an oven at 60℃ for 12 hours, and after baking was completed, the appearance and hardness of the adhesive film was observed, and if it was not completely dry, it was continued to be baked until it was completely dry.
[0087] b) The prepared adhesive film was cut into strips with scissors.
[0088] c) The strip of adhesive film was weighed, the initial weight a was recorded, and placed in a vial, and electrolyte (a solution in which the solvent was EC and DMC in a volume ratio of 1:1 and the concentration of LiPF6 by mass was 12.5% based on the mass of the electrolyte) was added, extending 2-3 cm beyond the adhesive film, the vial was sealed, and placed in a vacuum drying oven at a temperature of 85°C for 6 hours.
[0089] d) Measurement of the swelling degree of the adhesive film The adhesive film was taken out and wiped with clean paper, and the weight b of the adhesive film at this time was recorded. The swelling degree was calculated as follows: swelling degree = (ba) / a x 100%. Three parallel samples were prepared, and the swelling degrees obtained were arithmetically averaged to obtain the swelling degree of this functional layer.
[0090] 9. Flatness The flatness of the secondary battery was evaluated by a laser scanning method. Specifically, an optical device was used to scan the entire outline of the secondary battery to create a 3D model, and then the difference between the overall thickness and the cross-sectional thickness was calculated as P, and this difference was taken as the flatness of the secondary battery. If P≦0.5mm, the flatness of the secondary battery at that time met the requirements and was deemed OK. If P>0.5mm, the flatness at that time did not meet the requirements and was deemed NG.
[0091] 10. Nail penetration pass rate The secondary battery to be measured was charged at a constant current of 0.05C up to the designed full charge voltage, and then charged to 0.025C (cut-off current) at the designed full charge voltage to bring the secondary battery into a fully charged state, and the appearance of the secondary battery at this time was recorded. A nail penetration test was performed on the battery in an environment of 25±3°C. Here, the diameter of the steel nail was 4mm, the penetration speed was 30mm / s, and the nail penetration position was the geometric center of the secondary battery. The test was performed for 3.5 minutes or was stopped after the surface temperature of the electrode assembly dropped to 50°C. Ten secondary batteries were grouped into one group, and the state of the secondary batteries during the test was observed, and the judgment criterion was that the secondary batteries did not burn or explode.
[0092] 11. Impact test 1) Full charge: In an environment of 25±3℃, the battery was charged at a constant current (CC) rate of 0.7C up to 4.45V, then charged at a constant voltage (CV) rate of 0.02C up to 4.45V. The battery's open circuit voltage (OCV) / AC internal resistance (IMP) were measured and recorded, and then photographed.
[0093] 2) A round rod with a diameter of φ15.8±0.1 mm was placed in the center of the secondary battery (perpendicular to the tab direction).
[0094] 3) A weight of 9.1±0.1 kg was dropped vertically from a round bar to a height of 61±2.5 cm in a free state.
[0095] 4) After the surface temperature of the secondary battery dropped to 50°C, the test was stopped and the OCV / IMP was recorded and photographed.
[0096] 5) Ten secondary batteries were grouped into one group, and the condition of the secondary batteries was observed during the test. The criterion for judgment was whether the secondary batteries burned or exploded.
[0097] 12. Free fall test 1) The secondary battery was charged at a constant current (CC) of 0.5C up to 4.45V, then at a constant voltage (CV) of 0.02C at 4.45V until it was fully charged.
[0098] 2) After the sample was fully charged, the OCV and IMP of the sample were measured and recorded, and the appearance was inspected and photographed.
[0099] 3) The secondary battery was allowed to freely drop from a height of 1.8 m onto a smooth marble surface.
[0100] 4) Falling order (6 sides, 4 corners): front, right side, back, left side, top, bottom, top left, top right, bottom left, bottom right. One round consisted of each face / corner falling once in a row.
[0101] 5) After each test round was completed, the OCV and IMP were measured and recorded, and the appearance was inspected. Each group of samples was dropped five times, and 10 rechargeable batteries were classified into one group.
[0102] 6) All defective rechargeable batteries were photographed separately.
[0103] 7) After the drop was complete, the sample was left to stand for 24 hours, and the OCV and IMP were measured and recorded.
[0104] 8) After the test was completed, the appearance was inspected and photographed.
[0105] 9) The criteria for judging were that there was no damage, no leakage, no smoke, no fire, and a voltage drop of less than 15mV.
[0106] 13. 25℃ / 45℃ cycle capacity retention rate The cycle characteristics were evaluated in an environment of 25°C / 45°C (±3°C) using a Land CT2001A. The secondary battery was charged at a constant current of 0.2C to 4.45V, and then charged at a constant voltage of 4.45V until the current was less than 50μA. It was then discharged at a constant current of 0.2C to 3.0V. The discharge capacity of the first cycle was recorded as the initial capacity C0. The above charge / discharge cycle was repeated 500 times, and the discharge capacity of the 500th cycle was recorded as C500. The cycle capacity retention rate of the 500th cycle was C500 / C0×100%. Measurement results
[0107] [Table 1-1]
[0108] [Table 1-2]
[0109] From the data in Table 1, it can be seen that within a certain range, the thickness of the functional layer is an important factor that affects the electrolyte retention rate, the proportion of the wavenumber region of ≧1333 mV, flatness, and capacity retention rate, and that satisfying 5 μm≦H≦15 μm contributes to further improving the appearance flatness of the secondary battery and improving the characteristics in the later stages of cycling.
[0110] [Table 2-1] Note: All percentages of each binder component are by weight.
[0111] [Table 2-2]
[0112] From the data in Tables 2-1 and 2-2, it can be seen that the components of the binder directly affect the swelling degree of the functional layer, which in turn affects the electrolyte retention rate, the proportion of the wave number region of ≧1333 mV, the flatness, and the cycle capacity retention rate. In order to ensure the stability of the functional layer, the greater the swelling degree, the greater the electrolyte retention rate and the proportion of the wave number region of ≧1333 mV, and the better the corresponding battery capacity retention rate.
[0113] [Table 3-1] Note: All percentages of binder components are by weight.
[0114] [Table 3-2]
[0115] From the data in Tables 3-1 and 3-2, it can be seen that the type of inorganic particles affects the safety characteristics of secondary batteries. This is mainly because different types of inorganic particles have different morphologies, and the morphology of inorganic particles affects the appearance (e.g., flatness) of the coating layer, thereby affecting the safety characteristics of the battery. From the examples, it can be seen that the safety characteristics of secondary batteries are relatively good by using boehmite.
[0116] [Table 4-1]
[0117] [Table 4-2]
[0118] From the data in Tables 4-1 and 4-2, it can be seen that the coverage rate of the functional layer directly affects the safety characteristics and electrical characteristics of the battery, the higher the coverage rate, the better the battery characteristics, and when the coverage rate is 80% to 100%, the battery characteristics are better.
[0119] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the present invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the spirit, principle, and scope of the present invention.
Claims
1. 1. An electrochemical device comprising: the electrochemical device includes an electrode assembly; The electrode assembly includes an electrode piece, The electrode piece includes a current collector, the current collector includes a first region and a second region; an active material layer is provided in the first region; A functional layer is provided in the second region, the functional layer comprises an organic polymer and inorganic particles; When the thickness of the functional layer is H1, H1 satisfies 1 μm≦H1≦15 μm, The Dv90 of the inorganic particles satisfies 1 μm≦Dv90≦4.5 μm; Electrochemical equipment.
2. The electrochemical device according to claim 1 , wherein H1 satisfies 5 μm≦H1≦15 μm.
3. The inorganic particles are (a) the Dv10 of the inorganic particles satisfies 0.1 μm≦Dv10≦0.8 μm; (b) the Dv50 of the inorganic particles satisfies 0.5 μm≦Dv50≦2.0 μm; and (c) The Dv90 of the inorganic particles satisfies 1 μm≦Dv90≦2.5Dv50. The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
4. The electrochemical device according to claim 1 , wherein the coverage of the functional layer in the second region is 80% to 100%.
5. 10. The electrochemical device of claim 1, wherein the inorganic particles comprise at least one of boehmite, diaspore, alumina, barium sulfate, calcium sulfate, and calcium silicate.
6. 2. The electrochemical device of claim 1, wherein the organic polymer comprises a polymer of at least one of an acrylic monomer, an acrylate monomer, and a styrene monomer.
7. The functional layer is (d) the swelling degree of the functional layer is 200% to 800%; (e) According to thermogravimetry, the functional layer contains a substance having an exothermic peak in the range of 280°C to 460°C; and (f) the mass percentage of the organic polymer is 20% to 90% based on the mass of the functional layer; The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
8. The electrochemical device comprises: (g) the adhesive strength between the functional layer and the current collector is 100 N / m to 600 N / m; (h) measuring using a non-destructive ultrasonic intelligent diagnostic system, transmitting ultrasonic waves to the electrochemical device along a thickness direction of the electrochemical device, obtaining a signal feedback distribution map of the ultrasonic waves of the electrochemical device, and based on the area of the electrochemical device in the signal feedback distribution map, the proportion of the area of the region where the ultrasonic signal intensity is 1333 mV or more is 30% to 95%; (i) the flatness of the electrochemical device is 0 to 0.5 mm; The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
9. The electrode assembly is a wound electrode assembly, The electrochemical device according to claim 1 , wherein a second region is provided at a winding start end and a winding end of the current collector, and the functional layer is provided in the second region at the winding end.
10. An electronic device comprising an electrochemical device according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive plate and lithium ion battery
CN113078282A
Electrochemical device and electronic device
CN113711396A
Electrode assembly having insulating film formed on tab, method for manufacturing same, and lithium secondary battery comprising same
CN114128035A
Power storage element
JP2012209252A
Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
WO2017141791A1